2020
DOI: 10.3390/mi11040349
|View full text |Cite
|
Sign up to set email alerts
|

3D Hydrodynamic Focusing in Microscale Optofluidic Channels Formed with a Single Sacrificial Layer

Abstract: Optofluidic devices are capable of detecting single molecules, but greater sensitivity and specificity is desired through hydrodynamic focusing (HDF). Three-dimensional (3D) hydrodynamic focusing was implemented in 10-μm scale microchannel cross-sections made with a single sacrificial layer. HDF is achieved using buffer fluid to sheath the sample fluid, requiring four fluid ports to operate by pressure driven flow. A low-pressure chamber, or pit, formed by etching into a substrate, enables volumetric flow rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Miccio et al [ 15 ] have shown that a red blood cell can serve as an adaptive optofluidic microlens, which can be used in the application of blood diagnosis. Hamilton et al [ 16 ] developed a three-dimensional focusing device, which was integrated with optical waveguides and used to analyze fluorescent signals from beads in fluid flow. A prism can also be formed by injecting different fluids with different flow rates to a chamber to manipulate light [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Miccio et al [ 15 ] have shown that a red blood cell can serve as an adaptive optofluidic microlens, which can be used in the application of blood diagnosis. Hamilton et al [ 16 ] developed a three-dimensional focusing device, which was integrated with optical waveguides and used to analyze fluorescent signals from beads in fluid flow. A prism can also be formed by injecting different fluids with different flow rates to a chamber to manipulate light [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two other developments in the optofluidic biosensor field show promise for greater sensitivity and increased functionality. Hydrodynamic focusing is one such development, in which the flowing biosample is constrained, either two-or three-dimensionally, to a stream in a region smaller than the channel cross-section, illustrated in Figure 1 [13][14][15]. The intention for confining flow in this way is to produce fluorescence signals with less variation and force biosample velocity to be more uniform.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptual illustration of hydrodynamic focusing methods, with the sample streams given in blue and the buffer streams given in red: (a) A two-dimensional hydrodynamic focusing (2DHF) method has two inlets coming from the side to focus the sample horizontally; (b) A three-dimensional hydrodynamic focusing (3DHF) method has two inlets coming from top, bottom, and sides to focus the sample horizontally and vertically. This figure is cited from Hamilton et al in Micromachines [15] under Creative Commons Attribution License. This article will show how the expected fluorescence signal for a collection of biosamples will compare for biosensors that incorporate different flow focusing and illumination modalities.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics (e.g., width, velocity) of the sample flow core, which significantly determine the system performance, mainly depend on the hydrodynamic characteristic of the flows in the system, microstructure of the flow channel, etc. Some studies have focused on investigating the theoretical hydrodynamic mechanisms of fluids to optimise the sample flow core for different applications [8,9]. Wang et al analysed the focusing force exerted on the sample flow and particles in the sample flow core and found that it included the flow-induced drag force and inertial lift force.…”
Section: Introductionmentioning
confidence: 99%